A novel self-adaptive microalgae photobioreactor using anion exchange membranes for continuous supply of nutrients. (August 2016) - Fu, Qian; Chang, Hai-Xing; Huang, Yun; Liao, Qiang; Zhu, Xun; Xia, Ao; Sun, Ya-Hui
Graphical abstract: Highlights: A self-adaptive microalgae PBR using anion exchange membranes was proposed. The proposed photobioreactor can realize continuous supply of nutrients. The novel AEM-PBR performance was largely improved compared to PBRs. A maximum biomass concentration of 4.38 g/L was obtained with the AEM-PBR. Abstract: A novel self-adaptive microalgae photobioreactor using anion exchange membranes (AEM-PBR) for continuous supply of nutrients was proposed to improve microalgae biomass production. The introduction of anion exchange membranes to the PBR can realize continuous supply of nutrients at desired rates, which is beneficial to the growth of microalgae. The results showed that the maximum biomass concentration obtained in the AEM-PBR under continuous supply of nitrogen at an average rate of 19.0 mg N/L/d was 2.98 g/L, which was 129.2% higher than that (1.30 g/L) in a PBR with all the nitrogen supplied in batch at initial. In addition, the feeding rates of nitrogen and phosphorus were optimized in the AEM-PBR to maximize biomass production. The maximum biomass concentration of 4.38 g/L was obtained under synergistic regulation of nitrogen and phosphorus feeding rates at 19.0 mg N/L/d and 4.2 mg P/L/d. The AEM-PBR demonstrates a promising approach for high-density cultivation of microalgae.